THE EFFECT OF THERMAL DECARBONATION ON STABLE ISOTOPE COMPOSITIONS OF CARBONATES - Sharp Z.D.; Papike J.J.; Durakiewicz T. (My University, 2003)
Oxygen and C isotope compositions Of C02 gas released by thermal decomposition of siderite, calcite, and dolomite were measured using a new 'real-time' continuous-flow technique to determine whether fractionation associated with simple thermal decarbonation could explain the large isotopic variations and mineralogy such as those found in the ALH84001 meteorite. Oxygen and C isotope fractionation between calcite or dolomite and evolved C02 gas during thermal decarbonation in a 3 bar He pressure environment is very small. The 8 13 C and delta18O values of evolved C02 gas are nearly identical to those of the carbonate, very different from the calculated equilibrium delta18Ocalcite-CO2 value of -4 to -5%o at 800-900 'C or from previous experimental results of decarbonation in vacuum. The kinetic delta18Osiderite-CO2 values are -2%o, whereas A' 3C siderite-CO2 values increase logarithmically with time, from -I%o for the earliest stages of decarbonation to >5%o in the final stages. Incomplete siderite decomposition produces both magnetite (8110 = 3.5%o SMOW) and minor graphite. CO and 02 were detected during the decarbonation process. The data can be explained by simultaneous oxidation and reduction by the reaction.
Keywords: EFFECTS; TEMPERATURE; MINERALOGY; ISOTOPES; CARBON